ADAPTATION OF MANAGEMENT DECISIONS TO UNCERTAIN CONDITIONS: EXPERIENCE OF UKRAINIAN ENTERPRISES IN THE GARDENING AND PARK EQUIPMENT MARKET - ZYMA, Andriy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyses the impact of the war in Ukraine on the state and conditions of doing business for Ukrainian companies in the garden and park equipment market. It was found that companies in this market face the same problems as most businesses in Ukraine. It was established that the garden and park equipment market in Ukraine is gradually transforming, although it has not undergone radical changes. For a long time, the market leaders have been and remain Andreas Stihl LLC and Husqvarna Ukraine LLC, subsidiaries of international companies. Therefore, it was important to track the correspondence between the moods and expectations of businesses in Ukraine and abroad. It was found that the biggest problems faced by Ukrainian businesses and international companies due to the uncertainty and instability caused by the war in Ukraine are the unpredictability of the situation, disruptions in logistics supplies, a decline in customer solvency, and a shortage of qualified personnel. Many companies in the market under study are changing their strategies and development plans and diversifying their activities in order to adapt to changing conditions. An important observation and conclusion is that crisis conditions not only destroy established systems but can also become the basis for new opportunities that must be identified and exploited in a timely manner. The leaders in their fields and markets are those companies that use all possible ways and tools to reduce uncertainty in management decision-making - gathering information, analysing it, forecasting, modeling target values, and functional dependencies. Since the conditions of instability and political and economic uncertainty in Ukraine continue and will have a long-term impact, taking into account and reducing factors of uncertainty in the process of making management decisions by economic entities remains an important task that requires further study and improvement.